Penggunaan Aplikasi Pembelajaran PAI Berbasis E-Learning: Studi Kasus di Madrasah Tsanawiyah Lombok Timur - Khotimah Elsani, Baiq Husnul; Supardi, Supardi; Lubna, Lubna (MODELING: Jurnal Program Studi PGMI, 2024)
In the era of digitalization of education, the application of e-learning technology is expected to improve the quality and effectiveness of PAI learning. The focus of this research is the use of E-Learning based PAI learning applications. The method used in this research is qualitative research with a case study approach. Researchers analyze and describe findings in the field based on data sources which are strengthened by data findings and theories that are in accordance with the research theme. Data collection techniques in this research used observation, interviews and documentation methods. Meanwhile, data analysis uses thematic analysis through the stages of data reduction, data presentation, and drawing conclusions. The research results show that the e-learning based PAI learning application has a positive impact on students' learning motivation and their involvement in the learning process. Teachers feel helped by interactive features that make it easier to deliver material more interestingly and efficiently. This application makes it easier for teachers to find out the level of students' understanding of the material that has been taught. The word wall application also makes it easy for students so that students are motivated and enthusiastic in answering questions, besides making the class atmosphere more active and interactive.